ORGANIC BEEKEEPING - Carvalho, Leandra Silva; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2022)
With the growing search for healthy foods in the European and North American markets, Brazil has had an appreciation in honey production, which has made it the purest honey in the world. With beekeeping activity, there is the generation of income, employment, preservation and growth of fauna and flora and quality of life. This work aims to inform about organic honey production in the Brazilian scenario, focusing on the Northeast Region. The advantages of beekeeping, its importance, its products and conditions to be followed to have a pure honey without the use of antibiotics and pesticides, conditions related to climate and soil. The techniques to be used in production do not cause a negative impact on the environment, and the one that is handling the techniques. The demands for high quality products and competition in the world are ascended, realizes the great search for quality honey.